Plantago Major Treatment Enhanced Innate Antioxidant Activity In Experimental Acetaminophen Toxicity - Rina Haryani Osman Basah; Farida Hussan; Mohd Rafizul Mohd Yusof; Nur Aqilah Kamaruddin,; Faizah Othman (Elsevier Pte. Ltd., 2024)
Objective:To determine the effect ofPlantago major(P. major) extract on the liverinjury following acetaminophen (APAP) toxicity.Methods:The male Sprague Dawley rats (n= 38) were randomly divided into normalcontrol (n= 6) and experiment (n= 32) groups. The latter was subdivided into fourgroups and induced with APAP (1000 mg/kg) per oral, followed byP. majorextract andN-acetylcysteine orally to the respective groups for six days.Results:On the seventh day, the serum bilirubin, liver enzymes and tissue malondial-dehyde were increased in APAP groups whereas the total protein in serum, tissue su-peroxide dismutase and glutathione levels were reduced. The plant extract treatmentreduced the histological deteriorations such as aggregation of hepatocellular cords, for-mation of binucleated cells and vacuolisation of the cells with scanty cytoplasm. It alsorevealed significant reduction of malondialdehyde and increased level of superoxidedismutase and glutathione. Thefindings in the extract treated groups were comparable tothe group treated withN-acetylcysteine.Conclusions:In conclusion,P. majorcan enhance innate antioxidant activity andameliorate the APAP-induced liver injury.